Synthesis and biological evaluation of novel enol carboxamide derivatives of aspirin and diflunisal - Hassan, Mohamed K.; Al Mekhlafi, Sadik; Ibrahim, Doa'a Anwar (Journal of Chemical and Pharmaceutical Research, 2016)
A series of enol carboxamide derivatives (4, 7, 12 and 15) were synthesized from aspirin and diflunisal that conjugated with 2-amino-5 - (ethylthio)-1, 3, 4-thiadiazole, and 2-amino-6- (trifluoromethyl) benzothiazole using dicyclohexylcarbodimide (DCC) as coupling agent and their structures were confirmed by IR and 1H NMR spectra. The preliminary evaluation indicate that all tested compounds produced significant reduction of paw edema compared to propylene glycol 50% (control group) and also had shown lesser gastrotoxicity than their parent drugs. In addition, all tested compounds exhibited the maximal anti-inflammatory activity compared to their parent drugs (except for compound (12) which was less potent than diflunisal). Moreover, compound (15) showed the highest anti-inflammatory activity and showed least ulcerogenic effect. The result of this study indicates that the incorporation of the trifluoromethyl benzothiazole or ethylthio-1, 3, 4- thiadiazole pharmacophores into aspirin and diflunisal maintained or increased their anti-inflammatory activity and may increase selectivity towards COX-2 enzyme